SAINT JOAN - Shaw, Bernard (Maple, 2013)
Seventeen-year-old Joan of Arc is told by voices from God that she will drive the enemy English army from her beloved country and see the French king crowned at last. This peasant girl succeeds against all odds. Two years later, she is on trial for her life...The penalty will be death at the stake.